Pharyngeal Airway Space Changes after Single Mandibular and Two-Jaw Surgery in Patients with Skeletal Class II Malocclusion - Nurver Karslı; Ayşe Tuba Altuğ (Galenos Yayinevi, 2024)
Objective: To retrospectively evaluate the effects of single mandibular advancement (MA) and two-jaw surgery (2J-S) on the pharyngeal airway space (PAS) and hyoid position for the correction of skeletal Class II malocclusion. Methods: Eleven adult patients who underwent only MA surgery and twelve adult patients who underwent Le Fort I maxillary impaction-MA surgery (2-JS) were included in the retrospective study. A total of 46 cephalometric recordings obtained before (T1) and after treatment (T2) were examined. Craniofacial changes, area, and linear measurements of the pharyngeal airway and hyoid bone position were obtained in both groups. The Wilcoxon signed-rank test was used to evaluate time-dependent changes within groups. The Mann-Whitney U test was used to compare differences between groups. Results: Hyoid-Vert values increased significantly in both groups (MA, p<0.01; 2J-S, p<0.05); however, Hyoid-Hor values decreased significantly only in the 2J-S group (p<0.01). The anteroposterior dimensions of the airway increased in both groups, except for the PNS-P and PPS groups (p<0.01). Although a significant increase was observed in the nasopharyngeal area (A1) in the MA group (p<0.05), the decrease was found to be statistically significant in 2JG (p<0.01). Significant increases were found in the oropharyngeal (A2) and hypopharyngeal areas (A3) in both groups (p<0.01, p<0.05). Conclusion: Both surgical procedures for the correction of Class II malocclusion resulted in increased hypopharyngeal, oropharyngeal, and total airway measurements.